Development and Evaluation of an ICU Nurse Training Program on Oral Mucosal Pressure Injury Prevention and Management Using the ADDIE Model - Jia T; Lan Y; Pang J; Ma M; Ding Z; Wang Y; Jiang E (Risk Management and Healthcare Policy)
Tiantian Jia,1 Yunxia Lan,2 Jing Pang,2 Mengdan Ma,1 Zhe Ding,3 Yongting Wang,1 Enshe Jiang4 1Cardiac Surgery Intensive Care Unit, The Affiliated Chest Hospital of Zhengzhou University, Zhengzhou, 450008, People’s Republic of China; 2Department of Nursing, The Affiliated Chest Hospital of Zhengzhou University, Zhengzhou, 450008, People’s Republic of China; 3Department of Rehabilitation, The Affiliated Chest Hospital of Zhengzhou University, Zhengzhou, 450008, People’s Republic of China; 4Institute of Nursing and Health, Henan University, Kaifeng, 475004, People’s Republic of ChinaCorrespondence: Enshe Jiang, Institute of Nursing and Health, Henan University, No. 1 Jinming Road, Kaifeng, Henan, 475004, People’s Republic of China, Email esjiang@gmail.com Yongting Wang, Cardiac Surgery Intensive Care Unit, the Affiliated Chest Hospital of Zhengzhou University, No. 1 Weiwu Road, Zhengzhou, Henan, 450008, People’s Republic of China, Email 2313992171@qq.comPurpose: To construct a training course program for ICU nurses to care for oral mucosal membrane pressure injury (MMPI) and evaluate its implementation effects based on the ADDIE model.Patients and Methods: A research team was established to construct the training course program in January 2024. According to the ADDIE model, a training course was designed and developed after the literature research and Delphi expert inquiry. The training course program was implemented in 138 ICU nurses from a tertiary A hospital in China from April to May 2024. The ICU nurses’ knowledge, attitude, and practice in preventing medical device-related pressure injury in critically ill patients and the incidence of oral MMPI were compared before and after the training program.Results: A particular training course program for the ICU nurses to care for oral MMPI was constructed in this study. It contained three aspects of particular training subjects (professional knowledge, practical skills and professional literacy) and included 16 specific training courses. One hundred and thirty-eight ICU nurses received the training course program in the hospital. The total score of MMPI knowledge-attitude-practice of the ICU nurses was (167.73± 8.13) after the training, which was significantly improved compared with the score before the training (145.81± 13.57) (t = 16.283, P< 0.001). The incidence of oral MMPI after the training (5.94%) was significantly lower than that before training (22.93) (x2=12.034, P< 0.001).Conclusion: The training course program for ICU nurses to care for oral MMPI based on the ADDIE module can effectively improve ICU nurses’ comprehensive ability to prevent oral MMPI and reduce the incidence of oral MMPI. It can be applied in clinical nursing education and practice.Keywords: ADDIE model, ICU nurses, mucosal membrane pressure injury, training course